W (VI)-doped sodium manganate single-crystal positive electrode material, preparation method thereof and application of W (VI)-doped sodium manganate single-crystal positive electrode material in sodium-ion battery
W(VI)-doped sodium manganate single-crystal cathode material was synthesized by high-temperature pure oxygen solid-state method, which solved the structural degradation problem of P2-NaxMnO2 cathode material in sodium-ion battery, and achieved high cycle stability and excellent electrochemical performance, making it suitable for sodium-ion battery electrodes.
Patent Information
- Application Number
- CN202511530014.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2026-02-10
AI Technical Summary
Existing P2-NaxMnO2 cathode materials in sodium-ion batteries suffer from irreversible phase transitions, Mn3+ disproportionation reactions, and structural degradation and capacity loss due to defective phase behavior during the first charge-discharge cycle. Current improvement strategies have not yet adequately enhanced their cycle stability and electrochemical performance.
W(VI)-doped sodium manganate single-crystal cathode material was synthesized by a high-temperature pure oxygen solid-state method. By doping W(VI) in the P2-Na0.7MnO2.05 lattice, strong WO bonds and Mn-OW covalent bonds were formed, constructing a grain boundary-free structure, which enhanced the material stability and alleviated mechanical stress and electrolyte erosion.
It significantly improves the cycle stability and electrochemical sodium storage capacity of sodium-ion batteries, enhances the stability of the material structure, reduces electrolyte erosion, is suitable for sodium-ion battery electrodes, has a simple and easy-to-operate process, low cost, and good environmental performance.
Smart Images

Figure CN121506926A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of manganese-based sodium battery materials technology, specifically relating to a W(VI)-doped sodium manganate single crystal cathode material, its preparation method, and its application in sodium-ion batteries. Background Technology
[0002] The global energy structure is rapidly transitioning towards a cleaner and lower-carbon model, requiring breakthroughs in key material technologies for new energy storage batteries and the development of high-performance, long-life sodium-ion batteries. Among these, P2-Na... x MnO2 cathode material, as a candidate material for sodium-ion batteries, has advantages such as low cost and environmental friendliness, but its technical defects significantly restrict its practical application. According to existing research, its three core defects are as follows: (1) Irreversible phase transitions during charging and discharging lead to structural degradation; (2) Mn 3+ The disproportionation reaction and Jahn-Teller effect lead to capacity loss; (3) the "defect phase behavior" of the first charge and discharge cycle leads to low voltage and capacity loss. In order to improve the above defects, relevant R&D personnel have done a lot of work. For example, the team of Zhang Genqiang at the University of Science and Technology of China found through in-situ XRD that unmodified P2-Na x MnO2 cathode materials exhibit a P2-O2 phase transition during the first charge-discharge cycle. However, by modulating the oxidation-reduction reaction of oxygen anions, the modified cathode material achieves phase transition-free cycling, significantly improving structural stability. Existing technologies have reported the beneficial effects of tungsten doping on transition metal oxides (LiMO2, where M represents Ni, Co, Al, or Mn) in lithium-ion batteries. Tungsten doping can improve the capacity of nickel-rich layered oxide cathode materials in lithium-ion batteries. For example, in 2023, Gianluigi A. Botton's team prepared W-doped LiNiO2 (LNO) particles using mechanical fusion and co-precipitation methods to study changes in the structure and position of W. In-depth characterization results revealed the preferred positions and forms of W, as well as possible W variants in the new doped LiNiO2 (LNO) cathode material. In 2021, JRDahn's team prepared W-doped LiNiO2 cathode materials using WO3, Ni(OH)2, and LiOH·H2O as precursors via co-precipitation and studied the mechanism by which W doping improves electrode capacity retention. Yang-Kook Sun's team at Hanyang University in South Korea investigated tungsten-doped Li[Ni] 0.95 Co 0.04 Al 0.01 Electrochemical performance of the O2 cathode (W-NCA95). The microstructure-modified W-NCA95 exhibits a capacity of 242 mAh g / L. -1 The high initial capacity of (0.1C) and the retention of 77.4% of its initial capacity after 1000 cycles, compared to undoped Li[Ni] 0.95 Co0.04 Al 0.01 The capacity retention rate of O2 was only 14.5%.
[0003] Patent document CN202311835344.X discloses a P2-type tungsten-doped sodium-ion battery cathode material and its preparation method, which is prepared according to the following steps: weighing Mn2O3, Na2CO3, and Ni... 0.5 Mn 0.5 (OH)₂ and H₂WO₄ were mixed evenly in a mixer. The resulting powder was calcined in a muffle furnace at a heating rate of 2℃ / min to 600℃ and held for 8 hours. Then, it was cooled to 200℃ at a cooling rate of 20℃ / min to obtain intermediate product 1. Intermediate product 1 was heated to 1000℃ at a heating rate of 2℃ / min and held for 10 hours. Then, it was cooled to room temperature at a cooling rate of 20℃ / min to obtain intermediate product 2. Intermediate product 2 was subjected to a 5% sodium supplementation treatment. After being mixed evenly, it was heated to 600℃ in a muffle furnace at a heating rate of 2℃ / min and held for 6 hours. Then, it was cooled to room temperature at a cooling rate of 20℃ / min to finally obtain the W-doped P₂ phase sodium ion layered metal oxide cathode material Na. 0.67 Ni 0.35 Mn 0.64 W 0.01 O2. This patented technology uses a conventional roasting method to prepare Na. 0.67 Ni 0.35 Mn 0.64 W 0.01 O2 materials cannot guarantee Na 0.67 Ni 0.35 Mn 0.64 W 0.01 O2 materials are transformed from polycrystalline materials to monocrystalline materials.
[0004] To address the aforementioned shortcomings, current research mainly focuses on the following improvement strategies: (1) Element doping: By introducing elements such as W, Ti, Zn, and La, the layered structure is stabilized and phase transitions are suppressed; (2) Surface modification: Carbon coating or perovskite modification is used to reduce side reactions between the electrolyte and active materials, thereby improving interface stability; (3) Anion redox regulation: Activating oxygen anions to participate in charge compensation, replacing some transition metal redox reactions, and reducing structural stress. These improvement strategies have significantly improved P2-Na x The cycle life and rate performance of MnO2 have laid the foundation for its commercial application. However, the aforementioned improvement strategies still need further enhancement and optimization. Summary of the Invention
[0005] The key technical problem addressed by this invention is to provide a W(VI)-doped sodium manganate single-crystal cathode material, its preparation method, and its application in sodium-ion batteries. This method utilizes a simple experimental setup to synthesize the W(VI)-doped sodium manganate single-crystal cathode material via a high-temperature pure oxygen solid-state method. The prepared W(VI)-doped sodium manganate single-crystal cathode material, when used as an electrode in a sodium-ion battery, exhibits high specific energy and cycle stability. Specifically, W(VI) is doped with P2-Na. 0.7 MnO 2.05 After the cathode material lattice is formed, Na can be constructed. 0.7 W 0.01 Mn 0.99 O 2.05 In single-crystal cathode materials, the introduction of W(VI) has a positive effect on the material structure. The principal particles, mainly composed of manganese and oxygen, are the basic structural units of the material. After doping, these principal particles stack more tightly, orderly, and regularly in layers along specific crystallographic directions, effectively optimizing the arrangement of the principal particles. When W is doped into P2 layered oxides, it first forms strong WO bonds with O atoms, increasing the binding energy; then it shares O atoms with Mn atoms, forming Mn-OW covalent bonds, enhancing crystal structure stability and mitigating lattice expansion. This invention successfully prepared Na... 0.7 W 0.01 Mn 0.99 O 2.05 Single-crystal cathode materials possess a unique grain boundary-free structure. This characteristic effectively mitigates mechanical stress caused by volume changes during charge and discharge, preventing structural damage due to stress concentration. Simultaneously, the grain boundary-free structure reduces the contact area and penetration path between the electrolyte and the cathode material surface, significantly minimizing electrolyte erosion. These combined advantages result in a more stable cathode material structure during sodium-ion battery cycling, thus effectively improving the cycle stability of the battery. Therefore, Na… 0.7 W 0.01 Mn 0.99 O 2.05 Single-crystal cathode materials possess both excellent electrochemical sodium storage capacity and cycle stability, making them suitable for the fabrication of sodium-ion battery electrodes.
[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: a W(VI)-doped sodium manganate single-crystal cathode material, which has a P2-type layered structure and is in single-crystal form, and its general chemical formula is Na. x W y Mn 1-y O z , where 0.6≤x≤0.85, 0.005≤y≤0.02, 2.0≤z≤2.1.
[0007] Furthermore, the Na x W y Mn 1-y O z in y=0.01.
[0008] Furthermore, the Na x W y Mn 1-y O z for Na 0.7 W 0.01 Mn 0.99 O 2.05 .
[0009] Furthermore, the crystal structure of the W(VI)-doped sodium manganate single crystal cathode material contains a stable network structure composed of WO bonds and Mn-OW covalent bonds.
[0010] A method for preparing W(VI)-doped sodium manganate single crystal cathode material, the specific preparation process is as follows: sodium source, manganese source and tungsten source are weighed and mixed evenly according to the stoichiometric ratio of the general chemical formula, and the mixture is sintered at 800~900℃ for 4~12h in an oxygen-containing atmosphere to finally obtain W(VI)-doped sodium manganate single crystal cathode material.
[0011] Furthermore, the sodium source is NaOH, CH3COONa, Na2CO3, and NaHCO3; the manganese source is MnCO3, MnO2, or Mn2O3; and the tungsten source is WCl6 or W(NO3)6. The oxygen-containing atmosphere is a pure oxygen atmosphere. The heating rate of the high-temperature sintering is 3~10℃ / min.
[0012] Further, the specific preparation steps of the manganese source are as follows: NH4F is dissolved in ethylene glycol to obtain solution A, and (CH3COO)2Mn·4H2O is dissolved in ethylene glycol to obtain solution B; solution B is added to solution A and mixed evenly, and reacted at 60~80℃ for 4~8h. After the reaction is completed, the reaction solution is centrifuged and dried multiple times with ethylene glycol to obtain the precursor NH4MnF3, and then the precursor NH4MnF3 is heat-treated at 400~600℃ for 4~8h to obtain manganese source Mn2O3.
[0013] Further, the specific preparation steps of the W(VI)-doped sodium manganate single crystal cathode material are as follows: 3.605 mmol sodium source NaOH, 2.475 mmol manganese source Mn2O3, 0.05 mmol tungsten source WCl6, and anhydrous ethanol are sequentially added to an agate mortar, thoroughly ground into a slurry under a baking lamp, and dried. The slurry is then removed, ground into powder, placed in a porcelain boat, and then placed in a tube furnace purged with pure oxygen. The temperature is increased to 840-860℃ at a heating rate of 3-6℃ / min and held for 6-10 hours, finally yielding black Na... 0.7 W0.01 Mn 0.99 O 2.05 Single-crystal cathode material; W(VI) doped with P2-Na 0.7 MnO 2.05 After the cathode material lattice is formed, Na can be constructed. 0.7 W 0.01 Mn 0.99 O 2.05 In single-crystal cathode materials, the introduction of W(VI) has a positive effect on the material structure. The main particles, primarily composed of manganese and oxygen, are the basic structural units of the material. After doping, these main particles stack more tightly, orderly, and regularly in layers along specific crystallographic directions, effectively optimizing the arrangement of the main particles. When W(VI) is doped into P2 layered oxides, it first forms strong WO bonds with O atoms, increasing the binding energy; then it shares O atoms with Mn atoms, forming Mn-OW covalent bonds, enhancing crystal structure stability and mitigating lattice expansion. 0.7 W 0.01 Mn 0.99 O 2.05 Single-crystal cathode materials, due to their grain-bound nature, can effectively alleviate mechanical stress and reduce the erosion of the material by the electrolyte, thereby improving the cycle stability of sodium-ion batteries; this Na 0.7 W 0.01 Mn 0.99 O 2.05 Single-crystal cathode materials possess both excellent electrochemical sodium storage capacity and cycle stability, making them suitable for the fabrication of sodium-ion battery electrodes.
[0014] The W(VI)-doped sodium manganate single crystal cathode material of this invention is used to assemble sodium-ion batteries. The specific assembly process is as follows: W(VI)-doped sodium manganate single crystal cathode material is mixed with conductive agent acetylene black and binder polyvinylidene fluoride in a mass ratio of 7~8:1~2:1. N-methylpyrrolidone is used as solvent. The mixture is placed in an agate mortar and ground under an infrared lamp to obtain a slurry. The slurry is coated on current collector aluminum foil and transferred to a vacuum drying oven at 80~130℃ for 8 hours to prepare an electrode sheet with a diameter of 10~14mm. The electrode sheet is placed in a glove box filled with argon atmosphere for 1-4 hours to reduce the moisture adsorbed during the transfer process. Then, it is assembled into a CR2032 type coin cell in the glove box, using a circular commercial sodium sheet as the negative electrode, a 1mol / L NaClO4 solution as the electrolyte, and a 16mm diameter glass fiber membrane as the separator. After the battery is assembled, it is aged for 8 hours.
[0015] A sodium-ion battery comprising the W(VI)-doped sodium manganate single-crystal cathode material.
[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The W(VI)-doped sodium manganate single crystal cathode material (Na) prepared by the method of the present invention 0.7 W 0.01 Mn 0.99 O 2.05 Due to its absence of grain boundaries, it can effectively alleviate mechanical stress, reduce electrolyte erosion, and significantly improve battery cycle stability, making it of great value in the preparation of sodium-ion battery electrodes and the research of sodium energy storage devices.
[0017] (2) This invention successfully prepared W(VI)-doped sodium manganate single-crystal cathode material. During the doping process, W(VI) first forms a strong WO bond with O atoms to increase the binding energy, and then shares O atoms with Mn atoms to form a Mn-OW covalent bond, which enhances the stability of the crystal structure and slows down the lattice expansion. This W(VI)-doped sodium manganate single-crystal cathode material has excellent performance and great application potential, and is expected to be used in energy storage devices such as sodium-ion secondary batteries.
[0018] (3) The present invention has significant advantages, the process is simple and easy to operate, the experimental process is greatly shortened, the raw materials are easy to obtain and the cost is low, no toxic or harmful substances are generated in the entire preparation process, and the environmental protection is excellent; the overall conditions are mature, and it is very easy to move from the laboratory to large-scale industrial production. Attached Figure Description
[0019] Figure 1 A simplified diagram of the experimental setup for preparing cathode materials.
[0020] Figure 2 A comparison of the performance differences between polycrystalline and monocrystalline materials.
[0021] Figure 3 The XRD patterns of cathode materials prepared according to different raw material ratios are shown.
[0022] Figure 4 Raman spectra of cathode materials prepared with different raw material ratios.
[0023] Figure 5 The images shown are SEM and TEM images of the cathode material prepared in Example 1.
[0024] Figure 6 This is a long-cycle life test diagram of the cathode material prepared in Example 1. Detailed Implementation
[0025] The following examples further illustrate the above-described content of the present invention, but it should not be construed as limiting the scope of the subject matter of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention.
[0026] The following examples and comparative examples utilize experimental apparatus for preparing related materials using high-temperature solid-state reactions, such as... Figure 1As shown. Example
[0027] (1) 80.1 mmol of NH4F was dissolved in 120 mL of ethylene glycol to obtain solution A, and 7.34 mmol of (CH3COO)2Mn·4H2O was dissolved in 30 mL of ethylene glycol to obtain solution B. Both solutions were stirred until completely dissolved. Solution B was added to solution A and mixed evenly, and then the mixture was kept in an oven at 70 °C for 6 h. The reaction solution was centrifuged and dried several times with ethylene glycol to obtain the precursor NH4MnF3. Finally, the precursor NH4MnF3 was placed in a muffle furnace and heated to 500 °C at a heating rate of 1 °C / min and kept at that temperature for 6 h to obtain Mn2O3.
[0028] (2) Weigh the raw materials according to the ratio of 3.605 mmol NaOH, 2.475 mmol Mn2O3 and 0.05 mmol WCl6, add them to an agate mortar in sequence with anhydrous ethanol as solvent, grind them thoroughly into a slurry under an infrared lamp and dry them, take them out and grind them into powder, place them in a porcelain boat, and then put them into a tube furnace with pure oxygen, heat them to 850℃ at a heating rate of 5℃ / min and keep them at that temperature for 8h, finally obtaining the black positive electrode material Na 0.7 W 0.01 Mn 0.99 O 2.05 .
[0029] Comparative Example 1 (Polycrystalline Na) 0.7 MnO 2.05 (PC-NMO) (1) 80.1 mmol of NH4F was dissolved in 120 mL of ethylene glycol to obtain solution A, and 7.34 mmol of (CH3COO)2Mn·4H2O was dissolved in 30 mL of ethylene glycol to obtain solution B. Both solutions were stirred until completely dissolved. Solution B was added to solution A and mixed evenly, and then the mixture was kept in an oven at 70 °C for 6 h. The reaction solution was centrifuged and dried several times with ethylene glycol to obtain the precursor NH4MnF3. Finally, the precursor NH4MnF3 was placed in a muffle furnace and heated to 500 °C at a heating rate of 1 °C / min and kept at that temperature for 6 h to obtain Mn2O3.
[0030] (2) Weigh the raw materials according to the ratio of 3.605 mmol (3% excess) NaOH and 2.5 mmol Mn2O3, add them to an agate mortar in sequence with anhydrous ethanol as solvent, grind them thoroughly into a slurry under a baking lamp and dry them, take them out and grind them into powder, place them in a porcelain boat, and then put them into a tube furnace with pure oxygen, heat them to 800℃ at a heating rate of 5℃ / min and keep them at that temperature for 4h, finally obtaining the black positive electrode material Na 0.7 MnO 2.05 .
[0031] Comparative Example 2 (Single Crystal Na) 0.7 MnO2.05 (SC-NMO) (1) 80.1 mmol of NH4F was dissolved in 120 mL of ethylene glycol to obtain solution A, and 7.34 mmol of (CH3COO)2Mn·4H2O was dissolved in 30 mL of ethylene glycol to obtain solution B. Both solutions were stirred until completely dissolved. Solution B was added to solution A and mixed evenly, and then the mixture was kept in an oven at 70 °C for 6 h. The reaction solution was centrifuged and dried several times with ethylene glycol to obtain the precursor NH4MnF3. Finally, the precursor NH4MnF3 was placed in a muffle furnace and heated to 500 °C at a heating rate of 1 °C / min and kept at that temperature for 6 h to obtain Mn2O3.
[0032] (2) Weigh the raw materials according to the ratio of 3.605 mmol (3% excess) NaOH and 2.5 mmol Mn2O3, add them to an agate mortar in sequence with anhydrous ethanol as solvent, grind them thoroughly into a slurry under a baking lamp and dry them, take them out and grind them into powder, place them in a porcelain boat, and then put them into a tube furnace with pure oxygen, heat them to 850℃ at a heating rate of 5℃ / min and keep them at that temperature for 8h, finally obtaining the black positive electrode material Na 0.7 MnO 2.05 .
[0033] Comparative Example 3 (Adjusting the doping ratio) (1) 80.1 mmol of NH4F was dissolved in 120 mL of ethylene glycol to obtain solution A, and 7.34 mmol of (CH3COO)2Mn·4H2O was dissolved in 30 mL of ethylene glycol to obtain solution B. Both solutions were stirred until completely dissolved. Solution B was added to solution A and mixed evenly, and then kept in an oven at 70 °C for 6 h. The reaction solution was centrifuged and dried multiple times with ethylene glycol to obtain the precursor NH4MnF3. Finally, the precursor NH4MnF3 was placed in a muffle furnace and heated to 500 °C at a heating rate of 1 °C / min and kept at that temperature for 6 h to obtain Mn2O3; (2) Weigh the raw materials according to the ratio of 3.605 mmol NaOH, 2.4875 mmol Mn2O3 and 0.025 mmol WCl6, add them to an agate mortar in sequence with anhydrous ethanol as solvent, grind them thoroughly into a slurry under a baking lamp and dry them, take them out and grind them into powder, place them in a porcelain boat, and then put them into a tube furnace with pure oxygen, heat them to 850℃ at a heating rate of 5℃ / min and keep them at that temperature for 8h, finally obtaining the black positive electrode material Na 0.7 W 0.005 Mn 0.995 O 2.05 .
[0034] Comparative Example 4 (Adjusting the doping ratio) (1) 80.1 mmol of NH4F was dissolved in 120 mL of ethylene glycol to obtain solution A, and 7.34 mmol of (CH3COO)2Mn·4H2O was dissolved in 30 mL of ethylene glycol to obtain solution B. Both solutions were stirred until completely dissolved. Solution B was added to solution A and mixed evenly, and then kept in an oven at 70 °C for 6 h. The reaction solution was centrifuged and dried multiple times with ethylene glycol to obtain the precursor NH4MnF3. Finally, the precursor NH4MnF3 was placed in a muffle furnace and heated to 500 °C at a heating rate of 1 °C / min and kept at that temperature for 6 h to obtain Mn2O3; (2) Weigh the raw materials according to the ratio of 3.605 mmol NaOH, 2.4625 mmol Mn2O3 and 0.075 mmol WCl6, add them to an agate mortar in sequence with anhydrous ethanol as solvent, grind them thoroughly into a slurry under a baking lamp and dry them, take them out and grind them into powder, place them in a porcelain boat, and then put them into a tube furnace with pure oxygen, heat them to 850℃ at a heating rate of 5℃ / min and keep them at that temperature for 8h, finally obtaining the black positive electrode material Na 0.7 W 0.015 Mn 0.985 O 2.05 .
[0035] Comparative Example 5 (Adjusting the doping ratio) (1) 80.1 mmol of NH4F was dissolved in 120 mL of ethylene glycol to obtain solution A, and 7.34 mmol of (CH3COO)2Mn·4H2O was dissolved in 30 mL of ethylene glycol to obtain solution B. Both solutions were stirred until completely dissolved. Solution B was added to solution A and mixed evenly, and then kept in an oven at 70 °C for 6 h. The reaction solution was centrifuged and dried multiple times with ethylene glycol to obtain the precursor NH4MnF3. Finally, the precursor NH4MnF3 was placed in a muffle furnace and heated to 500 °C at a heating rate of 1 °C / min and kept at that temperature for 6 h to obtain Mn2O3; (2) Weigh the raw materials according to the ratio of 3.605 mmol NaOH, 2.45 mmol Mn2O3 and 0.1 mmol WCl6, add them to an agate mortar in sequence with anhydrous ethanol as solvent, grind them thoroughly into a slurry under a baking lamp and dry them, take them out and grind them into powder, place them in a porcelain boat, and then put them into a tube furnace with pure oxygen, heat them to 850℃ at a heating rate of 5℃ / min and keep them at that temperature for 8h, finally obtaining the black positive electrode material Na 0.7 W 0.02 Mn 0.98 O 2.05 .
[0036] Sodium-ion battery assembly is completed using the following method: The positive electrode materials obtained in Example 1 and Comparative Examples 1-5 were used as sodium electrode materials. They were mixed with conductive agent acetylene black (Super-p) and binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1, and ground in an agate mortar under infrared light using N-methylpyrrolidone (NMP) as solvent to obtain a slurry. The slurry was coated onto aluminum foil as a current collector and dried in a vacuum drying oven at 110°C for 8 hours to prepare an electrode sheet with a diameter of 10 mm. This electrode sheet was then placed in a glove box filled with argon atmosphere (water and oxygen content both below 0.1 ppm) for 3 hours to reduce moisture adsorbed during the transfer process. Finally, it was assembled into a CR2032 coin cell in the glove box. A 14 mm diameter circular commercial sodium sheet was used as the negative electrode, a 1 mol / L NaClO4 solution as the electrolyte, and a 16 mm diameter glass fiber membrane as the separator. After assembly, the battery was aged for 8 hours.
[0037] The battery was tested at a voltage of 1.8~4V and a current of 100mA g. −1 The discharge specific capacity after 100 cycles at the specified current density is shown in Table 1.
[0038] Table 1 Electrochemical properties of materials
[0039] As can be seen from the performance comparison data of Example 1 and Comparative Examples 1 and 2, the W(VI)-doped single-crystal cathode material Na prepared in this invention... 0.7 W 0.01 Mn 0.99 O 2.05 The overall electrochemical performance of the sample is significantly superior to that of the undoped polycrystalline and single-crystal comparative samples. Specifically, Comparative Example 1, as a traditional polycrystalline material, is prone to grain boundary cracking and structural damage during cycling, leading to loss of active material and rapid capacity decay. Example 1, employing a single-crystal structure, effectively avoids grain boundary problems, and W(VI) doping further stabilizes the crystal structure; both factors work together to achieve high battery capacity. While Comparative Example 2 achieved a high capacity retention rate (89.16%) due to its single-crystal structure, its intrinsic capacity is relatively low. Example 1, through W(VI) doping, forms strong WO bonds and Mn-OW covalent bonds, stabilizing the crystal structure and suppressing the P2-O2 phase transition; it may also optimize the diffusion kinetics of sodium ions, thus significantly improving the discharge capacity of the material while maintaining the advantages of the single-crystal structure.
[0040] In summary, the success of Example 1 is attributed to the synergistic effect of the single-crystal structure and W(VI) bulk doping. The single-crystal structure solves the mechanical failure problem caused by grain boundaries in polycrystalline materials, while W(VI) doping enhances structural stability and improves electrochemical activity at the atomic level. This comparison fully demonstrates the advancement and necessity of the technical solution of this invention (preparation of W(VI)-doped single-crystal cathode material).
[0041] Based on the performance comparison data of Example 1 and Comparative Examples 3-5, the influence of W(VI) doping amount on material properties is reflected in the following two aspects: On the one hand, insufficient W(VI) doping leads to poor performance: a small amount of W(VI) doping limits the number of W(VI) atoms entering the sodium manganate lattice, resulting in an insufficient number of strong TM-O-Mn (Mn-OW) covalent bonds, which cannot adequately suppress structural phase transitions and lattice expansion during charge and discharge. Simultaneously, although the WO bond energy is greater than the Mn-O bond energy, which helps weaken the interaction between Na and O and promotes sodium ion diffusion, the small amount of W(VI) doping results in very few WO bonds, which cannot effectively expand the interlayer spacing and stabilize the overall structure, ultimately leading to poor material capacity and cycle stability.
[0042] On the other hand, excessive W(VI) doping can also lead to performance degradation: (1) Destroying crystal structure stability: Excessive W(VI) ions can introduce excessive lattice stress, which may lead to local structural distortion and destroy the long-term cycling stability of the P2 layered structure. (2) "Poisoning" redox reactions: W(VI) is electrochemically inert within the voltage range of battery operation and does not participate in redox reactions. When excessive W(VI) replaces Mn, which is the main redox active center, it will directly lead to a reduction in the number of active ions that can participate in charge compensation in the material, thereby significantly reducing the intrinsic discharge specific capacity of the material. Comparative Example 4 has the worst performance, indicating that this doping amount may have reached a critical point, causing severe structural rigidity and capacity "poisoning". (3) Blocking sodium ion diffusion channels: Excessive and bulky W(VI) ions may occupy sites near the sodium ion layer or make the sodium ion migration path tortuous, thereby hindering the diffusion dynamics of sodium ions and affecting rate performance and reversible capacity.
[0043] The above embodiments describe the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are only illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from the scope of the principles of the present invention, and all such changes and modifications fall within the protection scope of the present invention.
Claims
1. A W(VI)-doped sodium manganate single-crystal cathode material, characterized in that: The cathode material has a P2-type layered structure and is in single-crystal form, with the general chemical formula Na. x W y Mn 1-y O z , where 0.6≤x≤0.85, 0.005≤y≤0.02, 2.0≤z≤2.
1.
2. The W(VI)-doped sodium manganate single-crystal cathode material according to claim 1, characterized in that: Statement Na x W y Mn 1- y O z Medium y=0.
01.
3. The W(VI)-doped sodium manganate single-crystal cathode material according to claim 1, characterized in that: Statement Na x W y Mn 1- y O z For Na 0.7 W 0.01 Mn 0.99 O 2.05 .
4. The W(VI)-doped sodium manganate single-crystal cathode material according to claim 1, characterized in that: The cathode material contains a stable network structure composed of WO bonds and Mn-OW covalent bonds in its crystal structure.
5. A method for preparing a W(VI)-doped sodium manganate single-crystal cathode material according to any one of claims 1 to 4, characterized in that... The specific preparation process is as follows: Sodium source, manganese source and tungsten source are weighed and mixed evenly according to the stoichiometric ratio of the general chemical formula. Under an oxygen-containing atmosphere, the mixture is sintered at a high temperature of 800~900℃ for 4~12h to finally obtain W(VI)-doped sodium manganate single crystal cathode material.
6. The method for preparing W(VI)-doped sodium manganate single-crystal cathode material according to claim 5, characterized in that: The sodium source is NaOH, CH3COONa, Na2CO3, and NaHCO3; the manganese source is MnCO3, MnO2, or Mn2O3; and the tungsten source is WCl6 or W(NO3)6. The oxygen-containing atmosphere is a pure oxygen atmosphere. The heating rate of the high-temperature sintering is 3~10℃ / min.
7. The method for preparing W(VI)-doped sodium manganate single-crystal cathode material according to claim 5, characterized in that... The specific preparation steps of the manganese source are as follows: NH4F is dissolved in ethylene glycol to obtain solution A, and (CH3COO)2Mn·4H2O is dissolved in ethylene glycol to obtain solution B; solution B is added to solution A and mixed evenly, and reacted at 60~80℃ for 4~8h. After the reaction is completed, the reaction solution is centrifuged and dried multiple times with ethylene glycol to obtain the precursor NH4MnF3, and then the precursor NH4MnF3 is heat-treated at 400~600℃ for 4~8h to obtain manganese source Mn2O3.
8. The method for preparing W(VI)-doped sodium manganate single-crystal cathode material according to claim 5, characterized in that... The specific preparation steps are as follows: 3.605 mmol of sodium source NaOH, 2.475 mmol of manganese source Mn2O3, 0.05 mmol of tungsten source WCl6, and anhydrous ethanol are sequentially added to an agate mortar. The mixture is thoroughly ground into a slurry under a heat lamp and then dried. The slurry is then ground into powder and placed in a porcelain boat. The boat is then placed in a tube furnace purged with pure oxygen and heated to 840-860℃ at a heating rate of 3-6℃ / min, and held at this temperature for 6-10 hours to finally obtain black NaOH. 0.7 W 0.01 Mn 0.99 O 2.05 Single-crystal cathode material; W(VI) doped into P2-Na 0.7 MnO 2.05 The cathode material lattice can construct Na 0.7 W 0.01 Mn 0.99 O 2.05 In single-crystal cathode materials, the introduction of W(VI) has a positive effect on the material structure. The main particles, primarily composed of manganese and oxygen, are the basic structural units of the material. After doping, these main particles stack more tightly, orderly, and regularly in layers along specific crystallographic directions, effectively optimizing the arrangement of the main particles. When W is doped into P2 layered oxides, it first forms strong WO bonds with O atoms, increasing the binding energy, and then shares O atoms with Mn atoms to form Mn-OW covalent bonds, enhancing crystal structure stability and mitigating lattice expansion. Na... 0.7 W 0.01 Mn 0.99 O 2.05 Single-crystal cathode materials, due to their grain-bound nature, can effectively alleviate mechanical stress and reduce the erosion of the material by the electrolyte, thereby improving the cycle stability of sodium-ion batteries; this Na 0.7 W 0.01 Mn 0.99 O 2.05 Single-crystal cathode materials possess both excellent electrochemical sodium storage capacity and cycle stability, making them suitable for the fabrication of sodium-ion battery electrodes.
9. The W(VI)-doped sodium manganate single-crystal cathode material according to any one of claims 1 to 4 is used to assemble a sodium-ion battery.
10. A sodium-ion battery, characterized in that... Includes the W(VI)-doped sodium manganate single crystal cathode material as described in any one of claims 1 to 4.
Citation Information
Patent Citations
P2-type tungsten-doped sodium ion battery positive electrode material and preparation method thereof
CN117638042A